2022
DOI: 10.3389/fphar.2022.848435
|View full text |Cite|
|
Sign up to set email alerts
|

A Novel N-Arylpyridone Compound Alleviates the Inflammatory and Fibrotic Reaction of Silicosis by Inhibiting the ASK1-p38 Pathway and Regulating Macrophage Polarization

Abstract: Silicosis is one of the potentially fatal occupational diseases characterized by respiratory dysfunction, chronic interstitial inflammation, and fibrosis, for which treatment options are limited. Previous studies showed that a novel N-arylpyridone compound named AKEX0011 exhibited anti-inflammatory and anti-fibrotic effects in bleomycin-induced pulmonary fibrosis; however, it is unknown whether it could also be effective against silicosis. Therefore, we sought to investigate the preventive and therapeutic role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In the initial stage of pneumoconiosis mechanism research, researchers found that with the progress of pneumoconiosis pathological process, the balance of oxidative stress was broken ( Liu et al., 2013 ). At the same time, the body occurs a chronic and progressive inflammatory reaction ( Fan et al., 2022 ). When threatened by environmental factors, the body produces SOD which is the first line of defense against oxidative stress ( Pardo and Selman, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the initial stage of pneumoconiosis mechanism research, researchers found that with the progress of pneumoconiosis pathological process, the balance of oxidative stress was broken ( Liu et al., 2013 ). At the same time, the body occurs a chronic and progressive inflammatory reaction ( Fan et al., 2022 ). When threatened by environmental factors, the body produces SOD which is the first line of defense against oxidative stress ( Pardo and Selman, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, dioscin can promote AM autophagy, enhance the clearance of mitochondria damaged by silica dust, and reduce the activation of mitochondria-mediated apoptosis pathway, so that AM resists apoptosis caused by silica dust and reduces the secretion of pro-inflammatory and profibrotic factors [48]. Moreover, AKEX0011, which is based on the phenylpyridone scaffold of pirfenidone, has been found to inhibit the Arabidopsis Serine/Threonine Kinase1 (ASK-1)/P38 signaling pathway and regulate the polarization of macrophages by reducing the phosphorylation of NF-κB/peroxisome proliferator-activated receptor gamma (PPAR-γ) proteins [71]. Atractylenolide III has also been shown to inhibit autophagy through an mTOR-dependent mechanism, improve the blockade of AM autophagy degradation, and reduce silicon-induced AM apoptosis [72].…”
Section: Autophagy and Apoptosismentioning
confidence: 99%
“…Tamoxifen, on the other hand, reduces the serum TGF-β1 content in rats in the model group in a dose-dependent manner, effectively inhibiting the process of silicosis [78], but also exhibits certain hepatotoxic effects. Interestingly, AKEX0011 has also been found to reduce the infiltration of neutrophils and macrophages in lung tissue and decrease the protein levels and mRNA expression of fibrosis-associated proteins [71]. Moreover, natural compounds such as ursolic acid and astragaloside IV can deactivate the mitogenactivated protein kinase (MAPK) signaling pathway, regulate PI3K/AKT/mTOR, inhibit the hyperphosphorylation of forkhead box O3 (FOXO3a) to inhibit EMT, and slow the progression of pulmonary fibrosis [79,80].…”
Section: Regulation Of Signaling Pathways Related To Emtmentioning
confidence: 99%
“…ASK1 kinase is the upstream molecule of p38 kinase and JNK kinase families. 88 It is regulated by tumor necrosis factor (TNF), transforming growth factor‐β (TGF‐β), Fas Ligand [FAS (Fas Cell Surface Death Receptor) is a protein coding gene's name] and more, and inhibited by the AKT kinase family. 89 ASK1 is a crucial cellular stress sensor, modulates diverse responses to oxidative and endoplasmic reticulum stress and calcium influx.…”
Section: Kinase Groupsmentioning
confidence: 99%
“…At present, no drug that specifically inhibits the ASK1 kinase family has been approved by the FDA, and no ASK1 kinase inhibitor has participated in human clinical trials 5 . Instead, some drugs, such as AKEX0011 88 and GS‐444217 91 are under basic experiments and have not yet received safety evaluation and clinical evaluation. Some scholars have also explored specific targeted inhibitory drugs through molecular docking and molecular dynamics 92 …”
Section: Kinase Groupsmentioning
confidence: 99%